Notae Ecclesiae: Dari Fungsi Eklesiologis ke Teologis - Laksito, Petrus Canisius Edi (Lux et Sal, 2023)
Unity, holiness, catholicity and apostolicity, or in Latin known as Notae Ecclesiae, are formulations of faith regarding the Church, confirming her essential attributes that make the Church the Church. In history, these attributes have made their contributions for the teaching of faith, for the apologetical tasks and, lately, as principles and criteria in doing Catholic theology. Thus, evidently, presenting the Church’s mysteries in their essential aspects, these notae have flexibility to be used as theological instruments in dogmatics, catechesis, apologetics, and even in theological methodology. Seeing these facts, it is hoped that dealing with these marks of the Church there are inspirations for further development for theology and also for the life of the Church.